A Systematic Literature Review on Bamboo Solvation in Formic Acid - Bautista, Ethan Benjamin D. (Animo Repository, 2022)
Bamboos are a diversified group of woody grasses that provide environmental, social, and economic benefits. The process of bamboo solvation is essential in many industries, instigating the search for a solution; however, it has proven to be a difficult process of solvent dissolution. Formic acids were proven to be an effective solvent among organosolvents, as they can fractionate different lignocellulosic biomasses. Thus, the study aims to conduct a systematic review of the literature on bamboo solvation using formic acid. The method and processes can be explained by systematically reviewing related literature on bamboo solvation, such as cellulose extraction as part of the process and the solvation process itself. The study compares formic acid with other known solvents used in bamboo solvation. In addition, the data and information gathered in this research shall be preserved and used for future use and execution. The efficiency, required conditions, advantages, and disadvantages of using formic acid in bamboo solvation shall be covered by this research. Bamboo solvation is performed because of its beneficial outcomes, benefiting businesses and companies, both the producers and consumers. These benefits include giving more knowledge on the versatile use of bamboo and giving factories a more biodegradable alternative to the consumers of their products.